Perjanjian Kemitraan Ekonomi Komprehensif Indonesia-Korea IK-CEPA - Muhammad Raihan; Berkat Perjuangan Ndruru; Tamaulina Br. Sembiring (PT. ALHAFI BERKAH INDONESIA, 2024)
Bilateral relations between Indonesia and South Korea have been well established for many years. This is proven by various collaborations carried out in various fields, including trade, investment, tourism and culture. One important form of cooperation is through bilateral agreements that have been signed by both countries. The Indonesia-Korea Comprehensive Economic Agreement Partnership (IK-CEPA) is a long bilateral agreement. Negotiations were halted in 2014 due to differences in agreement between the Korean and Indonesian governments. Then, in 2018, Korea agreed to reactivate the IK-CEPA agreement in response to the Indonesian government's request. This paper will discuss one of the important bilateral agreements between Indonesia and South Korea, namely the Comprehensive Economic Partnership Agreement (IK-CEPA). This agreement will be discussed in terms of its background, objectives, scope, benefits and challenges.